2017
DOI: 10.1177/0959683617702227
|View full text |Cite
|
Sign up to set email alerts
|

Holocene treeline and timberline changes in the South Carpathians (Romania): Climatic and anthropogenic drivers on the southern slopes of the Retezat Mountains

Abstract: Pinus cembra, Picea abies and Juniperus communis) reached Lake Lia between 12,000 and 11,800 cal. yr BP, whereas P. mugo colonised the shores of Lake Bucura at 9600 cal. yr BP.Lake Lia was in the timberline ecotone between 8000 and 3200 cal. yr BP, in semi-open P.cembra and Picea abies woodland, probably mixed with P. mugo on the steeper slopes. Lake Bucura was surrounded by the upper part of the krummholz zone during the mid-Holocene.The increase in P. cembra after c. 6000 cal. yr BP around Lake Lia suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 86 publications
2
13
0
Order By: Relevance
“…from the Retezat Mountains (South Carpathians, Romania) using multi-proxy methods to study the effect of and response to climate change and human impact by tree line, timberline, and alpine/subalpine vegetation during the past 16,000 years. It was concluded that climate change and human impact have both played an important role in lowering the tree line and timberline in the late-Holocene, and will continue to do so [35]. Therefore, with a background of climate warming, not all timberline areas can be generalized.…”
Section: Discussionmentioning
confidence: 99%
“…from the Retezat Mountains (South Carpathians, Romania) using multi-proxy methods to study the effect of and response to climate change and human impact by tree line, timberline, and alpine/subalpine vegetation during the past 16,000 years. It was concluded that climate change and human impact have both played an important role in lowering the tree line and timberline in the late-Holocene, and will continue to do so [35]. Therefore, with a background of climate warming, not all timberline areas can be generalized.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies from high mountains only single or a few sites have been investigated. Although some regional studies of European mountain regions synthesize data from multiple sites (Jouffroy-Bapicot et al, 2013;Treml, Jankovská, & Petr, 2008;Vincze et al, 2017), such studies rarely use multidimensional numerical methods to compare data from different sites and time periods (but see Feurdean, Willis, Parr, Tanţău, & Fărcaş, 2010;Feurdean et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the transition of ecosystem states, our method has made little progress in the identification of the alpine tree line location, and it is necessary to deeply explore the facilitation mechanism between different ecosystem states and the disturbances caused by the climate and by humans. In some areas, the alpine tree line has been shifted by anthropogenic impact [88] and global warming [17,89]. We have been to the Bogda for data acquisition and materials collection in 2017 and 2018, respectively.…”
Section: Discussionmentioning
confidence: 99%